Loss of long non-coding RNA CRRL promotes cardiomyocyte regeneration and improves cardiac repair by functioning as a competing endogenous RNA. (September 2018) - Chen, Guojun; Li, Hairui; Li, Xinzhong; Li, Bing; Zhong, Lintao; Huang, Senlin; Zheng, Hao; Li, Mengsha; Jin, Guoqing; Liao, Wangjun; Liao, Yulin; Chen, Yanmei; et al.
Abstract: Long noncoding RNAs (lncRNAs) play critical roles in the development of myocardial hypertrophy and may stimulate endogenous myocardial regeneration to prevent heart failure after myocardial infarction (MI). However, whether lncRNAs are involved in regulating myocardial regeneration after MI remains unclear. The present study aimed to identify human-derived lncRNAs that are involved in endogenous cardiomyocyte (CM) regeneration. By analyzing publicly available RNA-seq data of human fetal and normal adult cardiac tissues, we identified a novel human-derived adult upregulated lncRNA designated cardiomyocyte regeneration-related lncRNA (CRRL). Bioinformatics analysis indicated that CRRL is involved in the negative regulation of CM proliferation. First, we observed that the loss of CRRL attenuates post-MI remodeling and preserves cardiac function in adult rats. Through loss-of-function approaches, we found that CRRL knockdown promotes neonatal rat CM proliferation both in vivo and in vitro . Furthermore, we demonstrated that CRRL acts as a competing endogenous RNA (ceRNA) by directly binding to miR-199a-3p and thereby increasing the expression of Hopx, a target gene of miR-199a-3p and a critical negative regulatory factor of CM proliferation. Thus, CRRL suppresses cardiomyocyte regeneration by directly binding to miR-199a-3p, indicating that loss of CRRL facilitates myocardial regeneration and may be a new potential therapeutic strategy for heart failure. Graphical abstract: Unlabelled Image Highlights: CRRL was identified as a novel adult up-regulated lncRNA. Loss of CRRL promotes CM proliferation both in vivo and in vitro. Loss of CRRL improves cardiac repairs in neonatal and adult rats post-MI. CRRL regulates CM regeneration via CRRL/miR-199a-3p/Hopx regulatory loop.